1994
DOI: 10.1177/036354659402200209
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Intercondylar Notch by Plain Film Radiography and Magnetic Resonance Imaging

Abstract: The purpose of this investigation was twofold. In Part I, we determined the accuracy of morphometric analysis of the knee using magnetic resonance imaging and plain film radiography. The results of Part I validated the accuracy of magnetic resonance measurements and its superiority over plain film measurements. In Part II, we evaluated knee morphometry in 20 asymptomatic athletes with chronic anterior cruciate ligament insufficiency to determine if any predisposing factors to anterior cruciate ligament disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
2
15

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 11 publications
5
71
2
15
Order By: Relevance
“…This difference may be caused by different imaging techniques used for the evaluation of NWI. Two studies measuring NWI using MRI [8,21] have shown much higher values for normal adult populations than values reported in radiographic studies [2][3][4][5][6][7]20].…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…This difference may be caused by different imaging techniques used for the evaluation of NWI. Two studies measuring NWI using MRI [8,21] have shown much higher values for normal adult populations than values reported in radiographic studies [2][3][4][5][6][7]20].…”
Section: Discussionmentioning
confidence: 88%
“…Our report is the first, as far as we know, to use magnetic resonance imaging (MRI) to evaluate NWI in a population of skeletally immature patients. The imaging modality used to measure notch width has been the topic of considerable debate [5,8,[13][14][15][16]. Plain radiographic measurements of NWI are easy to obtain, but may be subject to patient positioning, variability in technique, projection and magnification [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations